Thermal Performance Simulation of an LTCC Micro-Reactor for RT-PCR in Detection of SARS-Cov-2 Detection - Kulhari, Lokesh; Suri, Nikhil; Ahmad, Badrul Hisham; Yupapin, Preecha; Ray, Kanad (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2022)
In present paper, thermal simulation of LTCC based micro-chamber has been performed which is a key part of RT-PCR device. The RT-PCR device plays an important role in SARS-CoV-2 testing. The rRT-PCR system requires three different thermal cycles for DNA amplification which takes part in detection of SARS-CoV-2. The thermal cycle can be equipped using a heater structure in the chamber. A new LTCC based technique to develop micro-chamber has been designed and simulation has been performed using COMSOL to optimize thermal properties. Temperature distribution for a micro-chamber at three different voltages has been simulated. The temperature distribution is more uniform in micro-chamber with a buried metallic layer in comparision to micro-chamber without a metallic layer. The heater and temperature sensor were located outside the reaction chamber. A platinum based pattern as PTC temperature sensor is used in temperature measurement.